Peran Lelang dalam Mendorong Pembangunan Ekonomi dan Hukum serta Peluang Digitalisasi Lelang di Indonesia: The Role of Auctions in Driving Economic and Legal Development and Opportunities for Auction Digitalization in Indonesia - Roby Putra, Aria (Faculty of Law, Universitas Brawijaya, 2026)
This study aims to analyze the role of auctions in driving economic and legal development and the opportunities for auction digitalization in Indonesia. This study is motivated by the lack of regulations that explicitly position auctions as a strategic instrument in national economic development, despite their important role in asset turnover, increasing state revenue, and providing legal certainty regarding the transfer of rights. The issues studied focus on the extent to which auction regulations in Indonesia have accommodated the role of auctions in supporting economic and legal development, and how the challenges of digitalization affect their implementation. The research method used is a normative juridical method with a statutory and conceptual approach. The results show that auction regulations in Indonesia are still oriented towards administrative and procedural aspects, thus not specifically regulating the function of auctions as a means of national economic development. The novelty of this study lies in the analysis of the importance of strengthening auction regulations as an instrument of economic and legal development through the integration of the principles of legal certainty, governance, and auction digitalization in Indonesia. Auctions contribute significantly to accelerating economic turnover and ensuring rights through legitimate and transparent legal mechanisms. In terms of governance, auctions can increase public accountability if supported by a system of oversight and integrity of auction officials. Meanwhile, digitalization opens up opportunities for greater efficiency and public participation, although infrastructure and data security challenges remain. Therefore, the synergy of regulations, technology, and human resource capacity is key to realizing a modern, fair, and sustainable national auction system.